Honey Accelerates Wound Healing in Pressure Ulcer: A Review - Halim, Jessica; Dwimartutie, Noto (Jurnal Plastik Rekonstruksi, 2020)
Introduction: Pressure ulcer (PU) is a result of prolonged pressure and shear over a bony prominence resulting in tissue injury of varying depth. To date, there is no standardized wound dressings for PU. Due to its availability and affordability, honey is suitable as PU wound dressing considering its anti-oxidant, anti-inflammatory, and antibacterial properties. This review article will provide evidence of the superiority of honey dressing.Methods: Literature source was searched through online databases with relevant keywords and then appraised for their validity, importance, and applicability. Total of three articles were appraised.Results: All articles agreed that application of honey on PU wounds reduced wound size and alleviate pain. Honey-impregnated gauze dressing promoted faster pain relief throughout treatment and less discomfort during each dressing change. Healing rate was proven 4 times faster with honey compared to other topical ointments. However, the antibacterial effect of honey was not significantly confirmed in the study. Nonetheless, topical application of honey successfully accelerates wound healing in PU.Conclusion: Honey is a promising alternative for topical dressings in patients with PU.